Organized crime requires dynamic decision making - Kerstholt, José; Keijser, Bas; Veldhuis, Guido; Smits-Clijsen, Eefje (Frontiers in Psychology, 2024)
It is extremely hard to successfully fight organized crime, not only because there are ambiguous and complex interactions between factors and actors, but also because organized crime is volatile and adaptive to changing conditions. This paper argues that, in addition to acquiring knowledge on criminal processes and behavior, we also need a better understanding of organizational decision-making processes to select the most effective and sustainable interventions aimed at organized crime. To date, one-shot decisions from a single organizational perspective are predominant in fighting organized crime. This type of decision often ignores the system response to the intervention. There is a need to acknowledge the dynamic nature of criminal behavior and networks, and to take that into account in the design of an intervention strategy. Such an approach entails a sequence of interdependent steps, iteratively applied, to reach sustainable effects. However, this way of decision making does not come naturally for most people. This paper concludes that investments should be made in training and decision support for teams fighting organized crime.